1976
DOI: 10.1508/cytologia.41.219
|View full text |Cite
|
Sign up to set email alerts
|

Studies in <i>Festuca</i> 7. Chromosome atlas (Part 2) An appraisal of chromosome race distribution and ecology, including <i>F. pratensis</i> var. <i>apennina</i> (De Not.) Hack, -tetraploid

Abstract: Studies in Festuca 7. Chromosome atlas (Part 2) An appraisal of chromosome race distribution and ecology, including F. pratensis var. apennina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…This means that the tetraploid and hexaploid races should be separable from octoploid and decaploid using this character. Seeds of many of the collections listed in Borrill, Tyler and Lloyd-Jones (1971) and Borrill, Tyler and Morgan (1976) have therefore been examined, confirming Saint Yves' observations. The 56 and 70 chromosome introductions had a conspicuous pubescence at the top of the caryopsis reminiscent of the appearance of F. donax and F. scariosa, but with fewer hairs.…”
Section: Observations On Caryopsis Apex Pubescencesupporting
confidence: 68%
“…This means that the tetraploid and hexaploid races should be separable from octoploid and decaploid using this character. Seeds of many of the collections listed in Borrill, Tyler and Lloyd-Jones (1971) and Borrill, Tyler and Morgan (1976) have therefore been examined, confirming Saint Yves' observations. The 56 and 70 chromosome introductions had a conspicuous pubescence at the top of the caryopsis reminiscent of the appearance of F. donax and F. scariosa, but with fewer hairs.…”
Section: Observations On Caryopsis Apex Pubescencesupporting
confidence: 68%
“…recorded by Borrill, Tyler & Morgan (1976). The diploid species F. pratensis, is distributed throughout the climatic regions of oceanic north-west Europe and the transitional oceanic/continental area of central Europe.…”
mentioning
confidence: 99%
“…Previous sampling had revealed only diploids and tetraploid cytotypes (Borrill et al, 1976;Tyler et al, 1978), but one report mentioned the recovery of triploid cytotypes (Tyler, 1988). Whilst the fertility of the triploid cytotypes was not assessed, it is expected that they had high sterility relying primarily on vegetative propagation for their widespread establishment.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative claims have been made that F. apennina is an autotetraploid cytotype of F. pratensis, or now and more widely accepted, an allotetraploid species derived from two ancestral progenitor species (Lewis, 1977;Jauhar, 1993). Borrill et al (1976) reported a different ecological and altitudinal distribution for the two fescue species with F. apennina absent below 1300 m above sea level (a.s.l. ), sometimes accompanied by F. pratensis in regions between 1300 and 1600 m a.s.l., but to its exclusion at higher altitudes.…”
Section: Introductionmentioning
confidence: 99%